N-Heterocyclic Pincer Dicarbene Complexes of Iron(II): C-2 and C-5 Metalated Carbenes on the Same Metal Center - Danopoulos, Andreas A.; Tsoureas, Nikolaos; Wright, Joseph A.; Light, Mark E. (Organometallics, 2004)
Six- and five-coordinate Fe(II) complexes with the pincer Iigand 2,6-bis(imidazolylidene)pyridine (C-N-C), [(C-N-C)Fe(MeCN)3][BPh 4]2 and [(C-N-C)FeBr2], respectively, were synthesized. Substitution of tmeda in [FeCl2(tmeda)]2 by C-N-C gave the sixcoordinate {[Fe(C-N-C)(C-N-C*)][FeCl4]}, in which one of the pincer ligands is bound to the metal via the 2- and 5-imidazole carbons.